Pharmacokinetic profile and quantitation of protection against soman poisoning by the antinicotinic compound MB327 in the guinea-pig. (26th February 2016) - Price, Matthew E.; Docx, Cerys J.; Rice, Helen; Fairhall, Sarah J.; Poole, Sarah J.C.; Bird, Michael; Whiley, Luke; Flint, Daniel P.; Green, A. Christopher; Timperley, Christopher M.; Tattersall, John E.H.
Highlights: The bispyridinium compound MB327 protects guinea-pigs from soman poisoning. Mode of action is not reliant on reactivation of aged inhibited acetylcholinesterase. First syntheses of d6-MB327 diiodide and dimethanesulfonate salts. Used as internal standards for mass spectrometric quantitation of MB327 in guinea-pig plasma. Abstract: Current organophosphorus nerve agent medical countermeasures do not directly address the nicotinic effects of poisoning. A series of antinicotinic bispyridinium compounds has been synthesized in our laboratory and screened in vitro. Their actions can include open-channel block at the nicotinic receptor which may contribute to their efficacy. The current lead compound from these studies, MB327 1, 1′-(propane-1, 3-diyl)bis(4- tert -butylpyridinium) as either the diiodide (I2 ) or dimethanesulfonate (DMS) has been examined in vivo for efficacy against nerve agent poisoning. MB327 I2 (0–113 mg kg −1 ) or the oxime HI-6 DMS (0–100 mg kg − 1 ), in combination with atropine and avizafone (each at 3 mg kg −1 ) was administered to guinea-pigs 1 min following soman poisoning. Treatment increased the LD50 of soman in a dose-dependent manner. The increase was statistically significant ( p  < 0.01) at the 33.9 mg kg −1 (MB327) or 30 mg kg −1 (HI-6) dose with a comparable degree of protection obtained for both compounds. Following administration of 10 mg kg −1 (i.m.), MB327 DMS reached plasma C max of 22 μM at 12 min with an elimination t 1/2 of 22 min. In an adverse effect study, in the absence of nerve agent poisoning, a dose of 100 mg kg −1 or higher of MB327 DMS was lethal to the guinea-pigs. A lower dose of MB327 DMS (30 mg kg −1 ) caused flaccid paralysis accompanied by respiratory impairment. Respiration normalised by 30 min, although the animals remained incapacitated to 4 h. MB327 or related compounds may be of utility in treatment of nerve agent poisoning as a component of therapy with atropine, anticonvulsant and oxime, or alternatively as an infusion under medical supervision.